Career Decision-Making in Indonesia: Cultural Values among Javanese, Sundanese, and Minangkabau - Noviati, Nur Pratiwi; Kadiyono, Anissa Lestari; Sulastiana, Marina; Lubis, Fitriani Yustikasari (MOTIVA: JURNAL PSIKOLOGI, 2025)
The purpose of this study is to explore the role of ethnic identity and cultural values in the career decision-making process among early-career employees from Javanese, Sundanese, and Minang ethnic groups in Indonesia. The research method used is qualitative with a phenomenological approach. The participants in this study were three early-career employees each representing one ethnicity. Participants were selected purposely and interviewed in depth. Data were analyzed using thematic analysis to identify relevant patterns and themes. The results of the study indicate that internal individual factors and cultural values can have a complex influence on individuals in making career decisions. The value of collectivism is found in the Javanese ethnic with the family philosophy of "mangan ora mangan sing penting ngumpul" (togetherness values). Likewise, the Sundanese ethnic group is known to prioritize the values of "luhur budi," "handap asor," and "someah hade ka semah," focusing on harmonious social relations, specifically by respecting others and choosing to avoid conflict. The Minang ethnic group found something different, namely the spirit of "merantau," where individuals prioritize proactive adaptation strategies based on high mobility to be able to seek opportunities outside their hometown. These differences indicate that cultural values can influence individuals' preferences, strategies, and ways of facing career challenges. Taken together, the dynamics of cultural values can be the basis for developing an adaptive career decision-making model. This research is expected to be the basis for designing culture-based interventions that support individuals in planning and managing their careers effectively.